2012
DOI: 10.1128/jvi.06889-11
|View full text |Cite
|
Sign up to set email alerts
|

The Amino Terminus of the Vaccinia Virus E3 Protein Is Necessary To Inhibit the Interferon Response

Abstract: Vaccinia virus (VACV) encodes a multifunctional protein, E3L, that is necessary for interferon (IFN) resistance in cells in culture. Interferon resistance has been mapped to the well-characterized carboxy terminus of E3L, which contains a conserved double-stranded RNA binding domain. The amino terminus of E3L has a Z-form nucleic acid binding domain, which has been shown to be dispensable for replication and IFN resistance in HeLa and RK13 cells; however, a virus expressing E3L deleted of the amino terminus ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 43 publications
2
52
1
Order By: Relevance
“…Thus, while the E3L ZBD has a nucleic acid-binding independent function to inhibit PKR, the nucleic binding property of this domain is important for viral pathogenicity. Taken together, these results lead us to suggest that the Z-DNA binding properties of E3L are necessary for the inhibition of other components of the interferon-induced anti-viral defense, consistent with the recent report that the pathogenicity of ΔE3L vaccinia virus is fully rescued by knockout of the type I interferon receptor in mice (White and Jacobs 2012).…”
Section: Discussionsupporting
confidence: 71%
“…Thus, while the E3L ZBD has a nucleic acid-binding independent function to inhibit PKR, the nucleic binding property of this domain is important for viral pathogenicity. Taken together, these results lead us to suggest that the Z-DNA binding properties of E3L are necessary for the inhibition of other components of the interferon-induced anti-viral defense, consistent with the recent report that the pathogenicity of ΔE3L vaccinia virus is fully rescued by knockout of the type I interferon receptor in mice (White and Jacobs 2012).…”
Section: Discussionsupporting
confidence: 71%
“…On the other hand, Zalpha domains are a feature of the poxviral protein E3L, which is present in all known poxviruses and which is crucial for the subversion of the host interferon response. The E3L protein acts through the inhibition of PKR (11) and has also been suggested to inhibit the action of DAI, a cytoplasmic sensor of nucleic acids with two Zalpha domains. Finding a similar virus evasion protein in Alloherpesviridae is consistent with previous work which identified similarities between genes encoding thymi-dylate monophosphate kinase (TmpK), ribonucleotide reductase and thymidine kinase in poxviruses and the family Alloherpesviridae, suggesting that Alloherpesviridae may be evolutionarily related to poxviruses (14).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, strains with nonfunctional E3L dramatically lose their proliferation potential. The E3L protein consists of two domains, a C-terminal dsRNAbinding domain (dsRBD) and an N-terminal Zalpha domain, and both domains have been shown to be required to fully block host responses (11). Surprisingly, however, no other virus family has been found to encode a Zalpha-containing protein.…”
mentioning
confidence: 99%
“…Moreover, we have previously demonstrated that a poxvirus E3L ortholog, such as sheeppox virus 034, does not supplement the biological functions of the E3 protein, although it binds dsRNA (18). It also has been reported that the ZBD plays a role in inhibition of interferon induction (19) and full pathogenesis in vivo in mice (14,20,21). Thus, it is inconclusive what role the biochemical capacity of dsRNA binding plays in the biological functions of the E3 protein.…”
mentioning
confidence: 95%
“…Since it has been reported that the N-terminal Z-DNA binding domain also is important for the complete biological functions of the E3 protein (14,(19)(20)(21), it would be interesting to examine the mutants (described in this report) in the system for identification of the biological functions of the Z-DNA binding domain. In addition, it will be interesting to investigate what correlation the described mutants will demonstrate with other reported functions attributed to vaccinia E3 protein, such as inhibition of cytokine in primary cells and dendritic cells (37,38) and inhibition of ISG15 (39).…”
Section: Figmentioning
confidence: 99%